Literatur Review : Masalah Homesickness yang Dihadapi Mahasiswa Baru di Perguruan Tinggi - Sakinatun Hasanah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This literature aims to find out about the problems and prevention of homesicknessexperienced by new students in tertiary institutions. and provide readers with an understanding of homesickness and how to prevent it. The various subtopics presented in this literature include factors of homesickness, impacts of homesickness, forms of homesickness, and prevention of homesickness, all of which are discussed in detail in this literature. The results of this study indicate that there are several factors that cause first-year students in tertiary institutions to experience homesickness, as it is known that if there is a cause and effect there must beprevention. This literature explains what to do when someone experiences a homesickness reaction such as positive thinking.